CGRaBS: An all-sky survey of gamma-ray blazar candidates - Healey, SE; Romani, R; Cotter, G; Michelson, P; Schlafly, E; Readhead, A; Giommi, P; Chaty, S; Grenier, I; Weintraub, L (2008)
We describe a uniform all-sky survey of bright blazars, selected primarily by their flat radio spectra, that is designed to provide a large catalog of likely γ-ray active galactic nuclei (AGNs). The defined sample has 1625 targets with radio and X-ray properties similar to those of the EGRET blazars, spread uniformly across the |b| > 10° sky. We also report progress toward optical characterization of the sample; of objects with known R < 23, 85% have been classified and 81% have measured redshifts. One goal of this program is to focus attention on the most interesting (e.g., high-redshift, high-luminosity,...) sources for intensive multiwavelength study during the observations by the Large Area Telescope (LAT) on GLAST. © 2008. The American Astronomical Society. All rights reserved.